The validity of using inertial measurement units to monitor the torso and pelvis sagittal plane motion of elite rowers - Brice, S. M.; Millett, E. L.; Philippa, B. (Journal of Sports Sciences, 2022)
In elite sport, inertial measurement units (IMUs) are being used increasingly to measure movement in-field. IMU data commonly sought are body segment angles as this gives insights into how technique can be altered to improve performance and reduce injury risk. The purpose of this was to assess the validity of IMU use in rowing and identify if IMUs are capable of detecting differences in sagittal torso and pelvis angles that result from changes in stroke rates. Eight elite female rowers participated. Four IMUs were positioned along the torso and over the pelvis of each athlete. Reflective markers surrounded each IMU which were used to compute gold-standard data. Maxima, minima, angle range and waveforms for ten strokes at rates of 20, 24, 28 and 32 strokes per minute were analysed. Root mean square errors as a percentage of angle range fell between 1.44% and 8.43%. In most cases when significant differences (p < 0.05) in the angles were detected between stroke rates, this was observed in both IMU and gold-standard angle data. These findings suggest that IMUs are valid for measuring torso and pelvis angles when rowing and are capable of detecting differences that result from changes in stroke rate.